SOLUSI PERSAMAAN DIFERENSIAL BOLTZMANN LINEAR - Agus Sugandha (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2009)
In this research, it will be discussed the way to find the solution of linear Boltzmann differential equation. The solution of linear Boltzmann differential equation is a fixed point of Markov Operator.